2019
DOI: 10.1097/md.0000000000014841
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of unplanned extubation in ordinary ward are similar to those in intensive care unit

Abstract: Unplanned extubation (UE) may cause considerable adverse effects in patients receiving mechanical ventilation (MV). Previous literature showed inconsistent prognosis in patients with UE. This study aimed to evaluate the clinical implications and outcomes of UE.The intubated adult patients with MV support in our hospital were enrolled, and they were divided into the UE and non-UE groups. Demographic data, admission unit, MV duration, overall weaning rate, and mortality rates were compared. The outcomes of UE in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…Reintubation is required for various reasons [ 3 ]. Lin P H and colleagues reported that reintubation cases due to accidental removal or self-removal of the tracheal tube both had distinct risk factors and prognoses [ 8 ]. In this study, we classified the unplanned reintubation cases by cause, excluded the non-respiratory cases, and mainly focused on AAC-caused reintubation after general anesthesia since the postoperative respiratory compromise cases stood out as the majority (36/48, 75.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Reintubation is required for various reasons [ 3 ]. Lin P H and colleagues reported that reintubation cases due to accidental removal or self-removal of the tracheal tube both had distinct risk factors and prognoses [ 8 ]. In this study, we classified the unplanned reintubation cases by cause, excluded the non-respiratory cases, and mainly focused on AAC-caused reintubation after general anesthesia since the postoperative respiratory compromise cases stood out as the majority (36/48, 75.0%).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, literature has shown that elderly critical patients had a greater rejection rate (18–36%) for ICU admission, when compared to the rejection rate (11–15%) of those aged < 65 years 25 . In some areas, a significant percentage (7.6–38.4%) of critical patients with IMV even had to stay in the general ward owing to shortage of ICU beds, and the condition was more severe for elderly patients (up to 51.1%) 7 , 26 , 27 . In the near future, many hospitals will be facing similar problems, when the increasing number of elderly patients with IMV exceeds the reserve of critical care manpower and resources.…”
Section: Discussionmentioning
confidence: 99%
“…Reintubation is required for various reasons [3] . Lin P H and colleagues reported that reintubation cases due to accidental removal or self-removal of the tracheal tube both had distinct risk factors and prognoses [8] . In this study, we classi ed the unplanned reintubation cases by cause, excluded the nonrespiratory cases, and mainly focused on AAC-caused reintubation after general anesthesia since the postoperative respiratory compromise cases stood out as the majority (36/48, 75.0%).…”
Section: Discussionmentioning
confidence: 99%